Efficiency of blood culture bottles for the fungal sterility testing of corneal organ culture media - Thuret, G (Copyright 2005 British Journal of Ophthalmology, 2005)
Background/aim: The consequences of fungal contamination of an organ cultured cornea, though exceptional, are often disastrous for the recipient. Consequently, eye banks often quarantine corneas for 10 days or more before passing them for grafting. This period, though detrimental to the endothelial cell density of the delivered cornea, is necessary to detect contamination using conventional microbiological methods. The authors previously validated the use of a pair of aerobic and anaerobic blood bottles for sensitive and rapid detection of bacteria. To allow a short quarantine period, it remained only to optimise detection of fungi. The authors aimed to compare sensitivity and rapidity of fungal contamination detection by three methods: blood bottles, Sabouraud, and daily visual inspection of the organ culture medium. Methods: Four inocula (10(6), 10(4), 10(2), 10 colony forming unit (CFU) per ml) of 11 fungi (Candida albicans, C tropicalis, C glabrata, Saccharomyces cerevisiae, Rhodotorula rubra, Cryptococcus neoformans, Fusarium oxysporum, Aspergillus niger, A fumigatus, A flavus, Acremonium falciforme) were inoculated in a commercial organ culture medium containing a coloured pH indicator (CorneaMax, Eurobio, Les Ulis, France). The real live fungal inoculum was verified immediately after inoculation. After 48 hours at 31°C, samples of the contaminated media were inoculated in three blood bottles: Bactec Aerobic/F, Bactec Mycosis IC/F, and Bactec Myco/F Lytic (Becton Dickinson, Le Pont de Claix, France), then placed in a Bactec 9240 rocking automat, and in four Sabouraud media (solid and liquid, 28°C and 37°C) with daily observation. Contaminated organ culture media were also checked daily for any change in turbidity and/or colour. Experiments were performed in triplicate. Results: Mycosis IC/F and Myco/F Lytic bottles were neither faster nor more sensitive than the aerobic bottle. The three methods were positive for all inocula, even the lowest (viable inoculum below 10 CFU/ml for each fungus). Contamination was detected within 24 hours by the aerobic bottles in 91% (40/44), by Sabouraud in 98% (43/44) (no significant difference) and by visual inspection in 66% of cases (29/44) (p<0.001 with the two others). Maximum times to detection were 46, 48 and 72 hours respectively. Conclusion: This study further counters the preconception that fungal contamination is hard to detect in corneal organ culture media. This study is the last step in validating the use of a pair of blood bottles for the sterility testing of organ culture media, this time for fungi. Their use should make it possible to shorten microbiological quarantine and thus deliver corneas with higher endothelial cell density, without increasing the risk of recipient contamination.